Information exchange model of multi control nodes in trustworthy and controllable network - WANG Peng; LUO Jun-zhou; LI Wei; ZHENG Xiao; QU Yan-sheng (Tongxin xuebao)
A new model based on two-layer Chord was proposed to realize information exchange between multi control nodes in trustworthy and controllable network.It constructs the two-layer Chord by constructing Chord between control nodes in AS and between ASes respectively.It uses this two-layer Chord to generate a two-layer aggregation tree automatically in exchanging process,which is used to realize basic information communication services.It provides AS administrative isolation for security and availability by guaranteeing path convergence for the same information in AS,and improves efficiency of communication.Meanwhile,it guarantees load balance between control nodes.Experiments verify that IEM has good performance.